2019
DOI: 10.14232/abs.2018.2.190-194
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in prevalence, parasite load and mean intensity of ectoparasites in Pipistrellus kuhlii (Chiroptera: Vespertilionidae) from Iran

Abstract: We studied quantitatively the seasonal variation in prevalence, parasite load, and mean intensity of two species of ectoparasites in free ranging populations of Kuhl's bat, Pipistrellus kuhlii in western Iran. In total, 348 live bats (230 males and 118 females) were collected using mist net during May to November 2013. All bats identified as to sex and the number of ectoparasite species in each bat was counted. On 348 P. kuhlii captured, 5355 ectoparasites were observed. Two species of ectoparasites belonging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a report by Tanalgo and Hughes (2019), more bat ectoparasite studies in the Philippines focused on new findings and bat hosts' distribution records (Alvarez et al 2015(Alvarez et al , 2016). In addition, several studies revealed parasite load correlates to the condition of bat health (Sharifi et al 2019), the decline of the population of specific species of bent-winged bats (Holz et al 2018), and the increased grooming behavior of bats (Obame-Nkoghe et al 2016). Much evidence also revealed differences in the relationship between bat sex and parasite load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a report by Tanalgo and Hughes (2019), more bat ectoparasite studies in the Philippines focused on new findings and bat hosts' distribution records (Alvarez et al 2015(Alvarez et al , 2016). In addition, several studies revealed parasite load correlates to the condition of bat health (Sharifi et al 2019), the decline of the population of specific species of bent-winged bats (Holz et al 2018), and the increased grooming behavior of bats (Obame-Nkoghe et al 2016). Much evidence also revealed differences in the relationship between bat sex and parasite load.…”
Section: Introductionmentioning
confidence: 99%
“…That could expose more females and juveniles to ectoparasites and ultimately affect females' reproductive success (Vidal et al 2021). In contrast, aggressive mating behavior in males may increase the chances of exposure and infection to parasites (Sharifi et al 2019). Furthermore, bat hosts' distribution range and size indicate parasite species wherein new species are documented to hosts distributed in larger areas (Maganga et al 2014).…”
Section: Introductionmentioning
confidence: 99%